Culturally Tailored Home-based Yoga Intervention for Lymphoma Patients on Chemotherapy - Gurpreet Kaur; Gaurav Prakash; Sukhpal Kaur; Mahender Singh; Sandhya Ghai; Alka Khadwal; Pankaj Malhotra (International Journal of Yoga)
Context: Although proven effective in solid cancers, there is a dearth of evidence-based studies supporting yoga as an intervention to improve health-related quality of life (HRQOL) among patients with lymphoma. Aim: The aim of this study was to develop a remotely supervised, home-based yoga intervention to improve HRQOL for lymphoma patients undergoing chemotherapy. Settings: This project was conducted at a tertiary care hospital in Northern India. Methodology: Experts in lymphoma, yoga, psychiatry, and nursing collaborated to formulate the intervention. Following a comprehensive literature review and stakeholder consultations, the intervention, named “Yoga Therapy” for patients with lymphoma, was developed. It included counseling regarding the benefits of yoga, a video and booklet on yoga, practical yoga sessions, telephonic support, regular follow-ups, random and need-based re-demonstrations, and adherence charts. The feasibility and safety of the intervention were assessed through a pilot study. Results: The developed intervention was found feasible, effective, and safe to be conducted during the pilot study. Reasonable adjustments were made in the final intervention to address individual needs, lymphoma burden, and other patient-specific concerns. Conclusion: The developed intervention was explicitly developed for patients with lymphoma during chemotherapy and seemed to be appropriate for its effectiveness testing during a randomized controlled trial.